Effectiveness of ethanol infusion into the vein of Marshall combined with a fixed anatomical ablation strategy (the "upgraded 2C3L" approach) for catheter ablation of persistent atrial fibrillation. (9th June 2021) - Lai, Yiwei; Liu, Xiaoxia; Sang, Caihua; Long, Deyong; Li, Mengmeng; Ge, Weili; Liu, Xiangfei; Lu, Zhibing; Guo, Qi; Jiang, Chao; Zuo, Song; Jiang, Chenxi; et al.
Abstract: Introduction: Linear ablation in addition to pulmonary vein antrum isolation (PVAI) has failed to improve the success rate for persistent atrial fibrillation (PeAF), due to incomplete block of ablation lines, especially in the mitral isthmus (MI). Methods and Results: The study enrolled 191 patients (66 in group 1 and 125 in group 2). In group 1, ethanol infusion into the vein of Marshall was first performed, followed by radiofrequency (RF) applications targeting bilateral PVAI and bidirectional block in the roofline, cavotricuspid isthmus, and MI. In group 2, PVAI and the three linear ablations were completed using only RF energy. MI block was achieved in 63 (95.5%) and 101 (80.8%) patients in groups 1 and 2, respectively ( p = .006). Patients in group 1 had shorter ablation time for left pulmonary vein antrum (8.15 vs. 12.59 min, p < .001) and MI (7.0 vs. 11.8 min, p < .001) and required less cardioversion (50 [78.5%] vs. 113 [90.4%], p = .007). During the 12‐month follow‐up, 58 (87.9%) patients were free from atrial fibrillation/atrial tachycardia in group 1 compared with 81 (64.8%) in group 2 ( p < .001). In multivariate cox regression, the "upgraded 2C3L" procedure is associated with a lower recurrence rate (hazard ratio = 0.27, 95% confidence interval = 0.12–0.59). Conclusion: Compared with the conventional "2C3L" approach, the "upgraded 2C3L" approach has higher effectiveness for ablation of PeAF.